2020
DOI: 10.1177/1098612x20907178
|View full text |Cite
|
Sign up to set email alerts
|

Serum allergen-specific IgE reactivity: is there an association with clinical severity and airway eosinophilia in asthmatic cats?

Abstract: Objectives The aim of this study was to evaluate the results of serum allergen-specific IgE testing in cats with a clinical diagnosis of asthma and to determine if the number of allergens with positive IgE reactivity and magnitude of positive IgE responses would be associated with the severity of clinical signs or airway eosinophilia. Methods Medical records from 2008 to 2018 were retrospectively reviewed. Inclusion required a diagnosis of feline asthma based on consistent clinicopathologic features and bronch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…11 Finally, a recent noncontrolled retrospective study reported intermediate and positive serum IgE responses in a majority (78%) of cats with respiratory signs related to eosinophilic airway disease. 13 We hypothesized that the number of cats with naturally occurring eosinophilic airway disease that produced allergen-specific IgE would be significantly higher than the number of control cats, which were matched for age and environment. We also hypothesized that the number of positive allergen reactions would be higher in affected as compared with control cats.…”
Section: Introductionmentioning
confidence: 99%
“…11 Finally, a recent noncontrolled retrospective study reported intermediate and positive serum IgE responses in a majority (78%) of cats with respiratory signs related to eosinophilic airway disease. 13 We hypothesized that the number of cats with naturally occurring eosinophilic airway disease that produced allergen-specific IgE would be significantly higher than the number of control cats, which were matched for age and environment. We also hypothesized that the number of positive allergen reactions would be higher in affected as compared with control cats.…”
Section: Introductionmentioning
confidence: 99%
“…62 A very recent retrospective study of 18 cats with a clinical diagnosis of asthma failed to show any association between the number and strength of allergen-specific IgE reactions on serology and the severity of clinical signs or airway eosinophilia. 63 The authors nonetheless concluded that there was a strong association between the identification of allergen-specific IgE in that 14 of the 18 cats (78%) showed positive reactivity. However, the absence of a control group raises questions as to the validity of this conclusion.…”
Section: The Role Of Antibodies In Spontaneous Feline Asthmamentioning
confidence: 99%
“…However, the absence of a control group raises questions as to the validity of this conclusion. 63 In the first and only study on the efficacy of ASIT for spontaneous feline asthma, IDT was performed on 20 cats that fulfilled the necessary clinicopathological diagnostic criteria. 64 Positive results were seen in 15 cats, mostly to HDMs and to a lesser extent, to pollens.…”
Section: The Role Of Antibodies In Spontaneous Feline Asthmamentioning
confidence: 99%
See 2 more Smart Citations